Politics, professionalism and performance management: a history of teacher evaluation in South Africa - Pillay, Devi (My University, 2018)
Why has South Africa failed to institute a teacher evaluation system that produces meaningful results? I aim to contribute to an understanding of why and how various South African post-1994 teacher evaluation policies have failed to become institutionalised and have failed to ensure either robust teacher accountability or professional development. In this dissertation, I examine the history of teacher evaluation in South Africa, in order to understand the evolution of these policies and systems over time. After discussing the legacy of apartheid-era evaluation, I assess three post-1994 policy phases: the 1998 Developmental Appraisal System (DAS), the 2001 Whole School Evaluation (WSE) policies and the 2003 Integrated Quality Management System (IQMS). This historical approach allows me to analyse the successes and failures of these policies in depth and context. Each of these policies has been shaped by, has tried to respond to, and has ultimately failed to confront the challenges of the past. They must also be understood to be a part of a continuous policymaking process, each one building upon and responding to the last. This dissertation contributes to an understanding of why these evaluation policies, despite massive investments of time, energy and resources, and complex and tough negotiations, have repeatedly failed. I argue that a flawed policy process consistently reiterates the same tensions and false assumptions in each new policy, and does not address these fundamental weaknesses. These appraisal policies reflect negotiations and contestations between teacher unions and the state, while the policies themselves and their outcomes further complicate those union-state relationships. The tensions and contradictions within these policies are the product of a policymaking process that tries to cater to mutually exclusive interests. The history of these institutions – teacher unions, the state, collective bargaining bodies – and the relationships between them must be understood in order to grapple with the policymaking environment fully. Further, even as these policies have been renegotiated and redeveloped, they have all failed to engage with the actual realities of teachers and classrooms in the majority of schools in South Africa. The legacy of apartheid education is still manifest in the abilities, attitudes and politics of teachers, and policymakers on all sides of the process have consistently failed to confront that history and propose real strategies for change.
A dissertation submitted to the University of the Witwatersrand, Johannesburg, in fulfilment of the degree Master of Arts in History by dissertation, 2018
Keywords: Teachers--Rating of--South Africa--History; Education--South Africa--Evaluation--History; Post-apartheid era--South Africa